Native phytotherapy for eye and ear complaints in Nasik District (Maharashtra) - Patil, M.V. (Medknow Publications & Media Pvt Ltd, 2008)
The tribals such as Kokana, Mahadeo-Koli, Bhil, Warali, Thakur, Katkari etc. and rural people of Nasik district use different parts of plants in crude form as cures against eye and ear afflictions. This paper deals with 13 plant species of which five species are employed by preparing formulations like juice, pulp and contact of drug in case of eye diseases. These are prepared from leaves, stem-bark and roots and administered for conjunctivitis, cataract and burning sensation of eyes. Likewise, eight species are used to cure ear-diseases by using drugs in the form of juice obtained from leaves, young stem-bark and fruits. Out of 13 species, five species each against eye and ear complaints are being reported for the first time. Modern laboratory methods and techniques are, however, required to reveal new lead molecules.